EARLY CHILDHOOD CARIES - PREVALENCE, PATHOGENESIS AND PREVENTIVE APPROACH: Narrative review of the literature - Ramos de Lucena, Bruna (2024)
Early childhood caries (ECC) is defined as a multifactorial and dynamic disease characterized by the presence of one or more carious surfaces (non-cavitated or cavitated lesions), absent (due to caries) or filled, in any deciduous tooth of a child under six years of age. Thus, the objective of this narrative review of the literature was to conduct a survey on the prevalence, pathogenesis and preventive approaches for early childhood caries. Publications by several authors in the format of scientific articles were used, which were available in virtual databases: Scientific Electronic Library Online (SciELO), PubMed and Google Scholar. The keywords used in the search were “early childhood caries”, “caries prevention”, “caries etiology” and pediatric dentistry and the same terms in English “early child caries”, “caries prevention”, “caries etiology” and “pediatric dentistry”. The narrative review of the literature presented brought a reflection on the high prevalence of early childhood caries around the world. Efforts should be made to address the child's condition in the first year of life, determining dietary advice, early hygiene care, rational use of fluoride and treatment techniques based on concepts of minimal intervention dentistry. Given this reality, it is necessary to highlight the relevance of the role of the dentist who treats children in the ongoing guidance of those responsible for the problem in question, contributing significantly to preventing and minimizing the impacts of caries on children's lives.